Gendered Difference in Agricultural Output: How Does Access to Land Contribute to the Debate? A Case Study of the Wa Municipality in Ghana - , Salisu Mustapha; , Barichisu Alidu; , Abdul-Aziz Baba Mustapha (Archives of Current Research International, 2017)
In Ghana like many other countries, gender plays a central role in the way in which land rights and production relations are determined. Whilst existing studies have suggested that men are economically productive than their women counterparts, those studies fail to emphasize the extent to which land, the most important input in developing economies’ agriculture, contribute to that difference. This study examined the gendered difference in agricultural output and the extent to which access to land contribute to the output difference using the t-test and the Kendall’s W. A sample of 100 farmers, 50 males and 50 females. Results show that whilst both men and women have reasonable access to land, men have access to land through multiple sources whilst women get land mostly through their spouses. The research also revealed that men’s output is significantly higher than their female counterparts partly due to the difference in farm size and also due to the limited access to farm inputs such as fertilizer and improved seeds.